“When Should I Tell?”: Perspectives on Disclosure to Their Children among Parents with Perinatally Acquired HIV - Fair, Cynthia D.; Allen, Hannah; Trexler, Constance; Osherow, Janet; D’Angelo, Lawrence (Frontiers in Public Health, 2016)
Adolescents and young adults (AYA) with perinatally-acquired HIV (PHIV) engage in developmentally-expected behaviors such as establishing relationships and having children. Previous research has focused on pregnancy management/outcomes of AYA with PHIV. However, little research has focused on the parenting experiences of this emerging cohort nor on their views of disclosure to their offspring. This article examines data from a pilot study of five AYA parents with PHIV on disclosure to their child(ren) (n=7, 6 HIV-negative). Disclosure of their own HIV status to their children is on the minds of parents with PHIV. However, few currently have children old enough to understand the parent’s diagnosis. Three parents indicated they would disclose their HIV status when their child was “old enough to understand” so that their child would be knowledgeable about HIV. One father also noted that he currently had more pressing parenting responsibilities beyond disclosure. When discussing their perspectives on disclosure, many referenced their personal stories indicating a link between their decision to disclose/not disclose to their child and their own disclosure narrative. One mother cited she did not plan to reveal her diagnosis to her son because he was uninfected while another mother explained she did not want to worry her child. The mother of the only infected child “did not want to wait like my mother did” and planned to tell her son at an earlier age than when she learned of her own diagnosis. Clinical implications related to disclosure will be discussed and future areas of research identified.